Six-Correction Logic (SCL) Gates in Quantum-dot Cellular Automata (QCA) - Md. Anisur Rahman; Sajjad Waheed; Md. Ahsan Habib; Ali Newaz Bahar (Chemical Engineering Diponegoro University, 2015)
Quantum Dot Cellular Automata (QCA) is a promising nanotechnology in Quantum electronics for its ultra low power consumption, faster speed and small size features. It has significant advantages over the Complementary Metal–Oxide–Semiconductor (CMOS) technology. This paper present, a novel QCA representation of Six-Correction Logic (SCL) gate based on QCA logic gates: the Maj3, Maj AND gate and Maj OR. In order to design and verify the functionality of the proposed layout, QCADesigner a familiar QCA simulator has been employed. The simulation results confirm correctness of the claims and its usefulness in designing a digital circuits.